PENGEMBANGAN BAHAN AJAR MATEMATIKA BERBASIS ALQURAN DI SEKOLAH DASAR - Ary Kiswanto Kenedi; Yullys Helsa; Sherlyane Hendri (Universitas Negeri Padang, 2018)
The purpose of this study is to produce teaching materials on learning mathematics based on the Qur'an in elementary schools are valid, practical and effective. This research is development research using the ADDIE model. The results showed that the developed teaching materials are categorized very valid with the percentage of teaching materials 91.50%. The effect of practicality test of teacher responsse is categorized very practical with percentage 91,07%, and student responsse is categorized very practical with percentage 92,04%. Assessment of learning outcomes of students is classified very high. Based on these results it can be concluded that the mathematics materials based on the Qur'an in elementary schools declared valid, practical and effective.Keywords: Al-quran, teaching material, mathematics, elementary school